Izbrane slogovne tendence sodobnih strokovnih besedil - k razvojnim spremembam sloga sodobnih čeških teoretično-strokovnih besedil - Schacherl, Martin (Jezik in slovstvo, 2018)
The aim of the paper is to provide evidence that the changing style of present-day Czech theoretical-scientific texts tends to exhibit greater inventiveness and individuality of authorial style. By exploring a representative selection of texts, the research attempted to verify the occurrence or non-occurrence of linguistic efforts that is deliberately used in contemporary Czech scientific discourse to disrupt (1) emotional and stylistic neutrality, and (2) the relative comprehensiveness, lucidity and clarity of professional expression. The analyses performed provided an insight into the potential processes currently gaining a footing in Czech theoretical discourse, i.e., processes resulting in obfuscation, emphasis on progressive aspects, interaction, individualisation, and the metaphorical quality of professional communication. The analyses of a representative corpus of five different groups of fields compiled for the purposes of the research failed to demonstrate a general shift of contemporary theoretical-professional communication in Czech from the 'Teutonic' to the 'Anglo-Saxon' style, although it is commonly assumed that such a change is underway.
Keywords: češčina; družboslovje; humanistika; slog; strokovna besedila; teoretični diskurz; znanstveni diskurz